749 Delivering Safe and Timely Cancer Care During COVID 19. Lessons and Successes from The Transition Period. (4th May 2021) - Dirie, J; Hart, E; Mahesan, T; Fawcett, W; Perry, M; Janardanan, S; Moschonas, D; Krishnaji, P; Chedid, W A
Abstract: Introduction: Delivering timely cancer care during the COVID-19 pandemic was a major challenge. We analysed our success in addressing this. Method: A key factor was the proximity of a private hospital (GN) to the primary trust. GN acted as a 'clean site'. From 6th April 2020, two robots and dedicated staff were relocated to day surgery theatres with direct access to GN. Procedures and post-operative recovery happened in GN. National surgical guidelines were followed related to Covid-19. All theatre staff were swabbed weekly. Patients were risk stratified prior to admittance. Results: We reviewed operations performed and cancer pathway data from March to June 2020 and compared it to data collected from August to November 2019. From March until June 2020 we performed 369 cancer operations; 120 robotic, 138 endoscopic and 7 open cases. From August to November 2019 we performed 407 cancer operations; 116 robotic, 175 endoscopic and 7 open cases. No elective patient developed symptomatic COVID-19 secondary to admission. Conclusions: This study demonstrates that with rapid development of separate 'clean' and 'COVID' sites, we successfully delivered a comparable, safe and effective cancer service. As we potentially face a second wave we share our success to see if these changes can be replicated elsewhere.